Sustainability transitions from the bottom-up: Civil society, the multi-level perspective and practice theory - Tom Hargreaves; Alex Haxeltine; Noel Longhurst; Gill Seyfang (University of East Anglia, The Centre for Social and Economic Research on the Global Environment (CSERGE), 2011)
This paper aims to build on an emerging trend in sustainability transitions research towards better understanding the potential roles played by civil society groups in transitions alongside state and market actors. Through the use of two empirical examples (a local and organic food producer cooperative called 'Eostre Organics' in East Anglia, UK, and the pro-environmental behaviour change programme 'EcoTeams'), the paper argues that whilst the Multi-Level Perspective on sustainability transitions is a valuable analytical tool to help conceptualise and distinguish between different kinds of civil society activity, its focus on single regimes and on novelty rather than normality means it cannot adequately capture the range or scope of civil society action. Here, we suggest that recent developments in Social Practice Theory, which explicitly address these concerns, offer a way to broaden and improve analyses. This leads us to re-examine a framework originally presented by Elizabeth Shove which draws attention to the connections and crossovers between these two theoretical approaches. The paper closes by exploring the gaps, limitations and implications of this framework for future research on the role of civil society groups in sustainability transitions.
Keywords: 330; civil society; social practice theory; sustainability transitions; the multi-level perspective